2012
DOI: 10.1021/mp300016p
|View full text |Cite
|
Sign up to set email alerts
|

Role of Antibody-Mediated Tumor Targeting and Route of Administration in Nanoparticle Tumor Accumulation in Vivo

Abstract: In this study, we have looked at enhancing tumor uptake and intracellular delivery of gold nanoparticles (AuNPs) while reducing the systemic exposure by systematic evaluation of the impact of targeting and route of administration on organ distribution. High-resolution microSPECT/CT imaging was used to track the in vivo fate of (111)In-labeled nontargeted and human epidermal growth factor receptor-2 (HER-2) targeted AuNPs following intravenous (i.v.) or intratumoral (i.t.) injection. For i.v. injection, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 43 publications
5
94
0
Order By: Relevance
“…The slow elimination of gold nanoseeds from the tumors was due to the properties of AuNP, which result in tumor retention after intratumoral injection (24). We previously found that 111 In-labeled AuNP modified with trastuzumab to target human epidermal growth factor receptor 2 was similarly retained by MDA-MB-361 human BC xenografts in mice after intratumoral injection, whereas intravenously injected AuNP were sequestered by the liver, spleen, and kidneys, greatly diminishing their tumor localization (24). OPSS-PEG-DOTA-177 Lu polymer not linked to AuNP injected intratumorally was ineffective for preventing tumor growth (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The slow elimination of gold nanoseeds from the tumors was due to the properties of AuNP, which result in tumor retention after intratumoral injection (24). We previously found that 111 In-labeled AuNP modified with trastuzumab to target human epidermal growth factor receptor 2 was similarly retained by MDA-MB-361 human BC xenografts in mice after intratumoral injection, whereas intravenously injected AuNP were sequestered by the liver, spleen, and kidneys, greatly diminishing their tumor localization (24). OPSS-PEG-DOTA-177 Lu polymer not linked to AuNP injected intratumorally was ineffective for preventing tumor growth (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This, together with the fact that I) the intratumoral penetration of nanomaterials with sizes exceeding ~10 nm tends to be poor [32][33][34] and that II) the presence of targeting ligands on the surface of nanocarriers generally has deleterious pharmacokinetic consequences (reducing their circulation half-life times and their passive EPR-mediated accumulation in tumors 11,27,29 ), calls for a systematic analysis of the benefit of active versus passive tumor targeting. Surely, under certain circumstances, e.g.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 99%
“…[6][7][8] Although many ligands demonstrate highly specific targeting ability in vitro, only a small number of them practically enhance the tumor accumulation of systemically administered NPs. [9][10][11][12][13][14][15] This limitation has inspired attempts to develop ligands for tumor-targeted applications with high efficiency.…”
Section: Introductionmentioning
confidence: 99%